USP33 regulates centrosome biogenesis via deubiquitination of the centriolar protein CP110. - Li, J; D'Angiolella, V; Seeley, E; Kim, S; Kobayashi, T; Fu, W; Campos, E; Pagano, M; Dynlacht, B (2013)
Centrosome duplication is critical for cell division, and genome instability can result if duplication is not restricted to a single round per cell cycle. Centrosome duplication is controlled in part by CP110, a centriolar protein that positively regulates centriole duplication while restricting centriole elongation and ciliogenesis. Maintenance of normal CP110 levels is essential, as excessive CP110 drives centrosome over-duplication and suppresses ciliogenesis, whereas its depletion inhibits centriole amplification and leads to highly elongated centrioles and aberrant assembly of cilia in growing cells. CP110 levels are tightly controlled, partly through ubiquitination by the ubiquitin ligase complex SCF(cyclin F) during G2 and M phases of the cell cycle. Here, using human cells, we report a new mechanism for the regulation of centrosome duplication that requires USP33, a deubiquitinating enzyme that is able to regulate CP110 levels. USP33 interacts with CP110 and localizes to centrioles primarily in S and G2/M phases, the periods during which centrioles duplicate and elongate. USP33 potently and specifically deubiquitinates CP110, but not other cyclin-F substrates. USP33 activity antagonizes SCF(cyclin F)-mediated ubiquitination and promotes the generation of supernumerary centriolar foci, whereas ablation of USP33 destabilizes CP110 and thereby inhibits centrosome amplification and mitotic defects. To our knowledge, we have identified the first centriolar deubiquitinating enzyme whose expression regulates centrosome homeostasis by countering cyclin-F-mediated destruction of a key substrate. Our results point towards potential therapeutic strategies for inhibiting tumorigenesis associated with centrosome amplification.